Copper winding with oil-sulfur corrosion resistance and preparation method thereof
By optimizing the rolling and annealing process of copper windings, copper windings with high content Σ3 grain boundaries and large grain size were prepared, which solved the problems of high oil sulfur corrosion inhibition cost and insufficient anti-corrosion measures of copper windings in the prior art, and achieved significant improvement in corrosion resistance of copper windings.
Patent Information
- Application Number
- CN202411562086.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art has problems such as high cost in suppressing oil-sulfur corrosion, inactive sulfur conversion, regular detection and addition of metal passivators, and fewer anti-corrosion measures for the copper winding itself.
By optimizing the rolling and annealing process of the copper winding, including rolling times ≥4, annealing temperature ≥300℃, annealing time ≥30 minutes, surface oxide was removed, and copper windings with a grain boundary content of >30% and a grain size >20 μm were prepared.
It significantly improves the oil-sulfur corrosion resistance of the copper winding, reduces the corrosion potential and current density, extends the insulation strength of the insulating paper, and improves the electrical performance of the insulating oil.
Smart Images

Figure CN119069252B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corrosion and protection of power grid materials, and more specifically, to a copper winding with oil-sulfur corrosion resistance and a preparation method thereof. Background Art
[0002] As an important component of oil-immersed transformers, copper windings react with corrosive sulfides (such as DBDS) in insulating oil. When the corrosion is severe, a large amount of visible corrosion products will be deposited on the insulating paper wrapped around the copper conductor, which will reduce the insulation strength of the insulating paper. In addition, the corrosion products deposited on the insulating paper will cause the insulation failure of the insulating paper to be broken down prematurely, eventually causing the transformer winding to discharge, and even causing the equipment to break down and burn in severe cases. Therefore, improving the oil-sulfur corrosion resistance of copper windings is crucial to the safe operation of the power grid system.
[0003] At present, the measures to inhibit oil-sulfur corrosion in engineering are mainly aimed at insulating oil, such as strict acceptance of new oil or adding metal passivators to inhibit the occurrence of corrosion. Although the above measures have improved the oil-sulfur corrosion resistance of copper windings to a certain extent, there are still some problems: for example, the cost is high and inactive sulfur will be converted into active sulfur (1ppm) during operation, the content of metal passivators in the oil needs to be regularly tested and metal passivators need to be added to the oil regularly, and the stray gases generated by the passivators will interfere with the fault diagnosis results of dissolved gases in the insulating oil.
[0004] In addition, there are currently few anti-corrosion measures for the copper windings themselves in oil-immersed power equipment. Therefore, it is urgent to propose new anti-corrosion measures for the copper windings themselves to improve the oil-sulfur corrosion resistance of the copper windings, so as to effectively improve the oil-sulfur corrosion resistance of the copper windings. Summary of the invention
[0005] In view of the above problems, the present invention provides a copper winding with oil-sulfur corrosion resistance and a preparation method thereof.
[0006] According to one aspect of the present invention, there is provided a method for preparing a copper winding having resistance to oil-sulfur corrosion, comprising: rolling a copper bar according to a predetermined number of passes to obtain a rolled winding; wherein the predetermined number of passes is ≥4; annealing the rolled winding at a predetermined temperature to obtain a copper winding to be treated; wherein the predetermined temperature is ≥300°C; and removing oxides attached to the surface of the copper winding to be treated to obtain a copper winding having resistance to oil-sulfur corrosion.
[0007] According to an embodiment of the present invention, the rolled winding is annealed at a predetermined temperature to obtain the copper winding to be processed, including: annealing the rolled winding at a predetermined temperature for a predetermined time to obtain the copper winding to be processed; wherein the predetermined time is ≥30min.
[0008] According to an embodiment of the present invention, the predetermined temperature includes 300-600°C.
[0009] According to an embodiment of the present invention, the deformation of the winding after rolling is ≥20%.
[0010] Another aspect of the present invention provides a copper winding having resistance to oil-sulfur corrosion, wherein the content of Σ3 grain boundaries in the copper winding having resistance to oil-sulfur corrosion is greater than 30%.
[0011] According to an embodiment of the present invention, the grain size in the copper winding having oil-sulfur corrosion resistance is greater than 20 μm.
[0012] According to an embodiment of the present invention, when the content of Σ3 grain boundaries is the same, the oil-sulfur corrosion resistance of the copper winding is positively correlated with the grain size.
[0013] According to the embodiment of the present invention, under the condition of the same grain size, the oil-sulfur corrosion resistance of the copper winding is positively correlated with the Σ3 grain boundary content.
[0014] According to an embodiment of the present invention, the corrosion potential of the copper winding includes: -0.21~-0.22V.
[0015] According to an embodiment of the present invention, the corrosion current density of the copper winding includes: 7.18×10 -8 ~2.65×10 -7 .
[0016] According to an embodiment of the present invention, by controlling the process parameters of the actual production process of the copper winding in the oil-immersed power equipment, such as the rolling pass, annealing temperature, predetermined annealing time, rolling deformation, etc., the process parameters for the preparation of the copper winding are optimized, and the above-mentioned method for preparing the copper winding with oil-sulfur corrosion resistance is used to obtain a copper winding with oil-sulfur corrosion resistance having a Σ3 grain boundary content of >30% and a grain size of >20 μm. The oil-sulfur corrosion resistance of the copper winding with oil-sulfur corrosion resistance provided by the present invention is greatly improved, and at the same time, based on improving the oil-sulfur corrosion problem of the copper winding in the power equipment from the copper winding itself, a new anti-corrosion measure to improve the oil-sulfur corrosion resistance of the copper winding is proposed. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and other objects, features and advantages of the present invention will become more apparent through the following description of the embodiments of the present invention with reference to the accompanying drawings, in which:
[0018] Figure 1 A flow chart showing a method for preparing a copper winding having oil-sulfur corrosion resistance according to an embodiment of the present invention is shown;
[0019] Figure 2 A diagram showing the relationship between the predetermined pass number and the content of special grain boundaries inside the winding according to an embodiment of the present invention;
[0020] Figure 3 The electrochemical polarization curves of the windings obtained by rolling with different predetermined passes according to the embodiment of the present invention are shown;
[0021] Figure 4 The copper content test results of the windings obtained by rolling at different predetermined passes according to the embodiment of the present invention are shown;
[0022] Figure 5 The breakdown voltage test results of insulating oil after different predetermined test times according to an embodiment of the present invention are shown;
[0023] Figure 6 The dielectric loss test results of the insulating oil after different predetermined test passes according to the embodiment of the present invention are shown;
[0024] Figure 7 The volume resistivity test results of the insulating oil after different predetermined test passes according to an embodiment of the present invention are shown;
[0025] Figure 8 The electrochemical polarization curves of the windings obtained at different annealing temperatures according to the embodiment of the present invention are shown;
[0026] Fig. 9 The copper content test results of the windings obtained at different annealing temperatures according to the embodiment of the present invention are shown;
[0027] Fig.10 The breakdown voltage test results of the insulating oil after different annealing temperature tests according to the embodiment of the present invention are shown;
[0028] Fig.11 The dielectric loss test results of the insulating oil after different annealing temperature tests according to the embodiment of the present invention are shown;
[0029] Fig.12 The volume resistivity test results of the insulating oil after different annealing temperature tests according to the embodiment of the present invention are shown;
[0030] Fig.13 The thermal conductivity test results of the insulation paper at different annealing temperatures according to the embodiment of the present invention are shown;
[0031] Fig.14 The results of the polymerization degree test of the insulating paper at different annealing temperatures according to the embodiment of the present invention are shown;
[0032] Fig.15 A diagram showing the relationship between the predetermined pass number and the CSL grain boundary ratio inside the winding according to an embodiment of the present invention;
[0033] Fig.16 A graph showing the relationship between the annealing temperature and the CSL grain boundary ratio inside the winding according to an embodiment of the present invention;
[0034] Fig.17 The test results of winding grain size at different annealing temperatures according to an embodiment of the present invention are shown;
[0035] Fig.18a A graph showing the relationship between the content of special grain boundaries inside the winding and the grain size according to an embodiment of the present invention is shown;
[0036] Fig.18b A graph showing the relationship between the internal grain size of the winding and the special grain boundary content according to an embodiment of the present invention;
[0037] Fig.19a The electrochemical polarization curves of windings with different grain sizes according to an embodiment of the present invention are shown;
[0038] Fig.19b The electrochemical polarization curves of windings with different special grain boundary contents according to an embodiment of the present invention are shown;
[0039] Figure 20a-Figure 20b The test results of the copper element content on the insulating oil / paper with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are shown respectively;
[0040] Figure 21a-Figure 21b The breakdown voltage test results of insulating oils with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are respectively shown;
[0041] Figure 22a-22b The dielectric loss test results of insulating oils with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are respectively shown;
[0042] Figure 23a-23b The volume resistivity test results of insulating oils with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are shown respectively. DETAILED DESCRIPTION
[0043] Below, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of concepts of the present invention.
[0044] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0045] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.
[0046] Power transformers are the core equipment for energy transmission and distribution in power grid systems. Once a failure occurs, it will bring immeasurable economic losses and serious safety issues to society. In recent years, power transmission and transformation equipment failures caused by the influence of corrosive sulfur in insulating oil on transformer windings have occurred frequently, which has attracted the attention of many research institutions at home and abroad.
[0047] As an important component of oil-immersed transformers, copper windings will react with corrosive sulfides (such as DBDS) in insulating oil. When the corrosion is severe, the insulating paper wrapped around the copper conductor will deposit a large amount of visible corrosion products. Tests have found that the main components of the corrosion products on the insulating paper are Cu2S and Cu2S. The insulation strength of the corrosion products is much lower than that of the insulating paper. Therefore, a large amount of corrosion products deposited on the insulating paper will cause the insulation strength of the insulating paper to decrease. In addition, the corrosion products deposited on the insulating paper will cause local electric field distortion of the insulating paper, which will further increase the local temperature of the insulating paper. At the same time, due to the presence of corrosion products, the heat of the winding is difficult to transfer, causing the insulation failure of the insulating paper to be broken down in advance, and finally causing the transformer winding to discharge, and even causing the equipment to break down and burn in severe cases. Therefore, improving the oil-sulfur corrosion resistance of copper windings is crucial to the safe operation of the power grid system.
[0048] At present, the measures to inhibit oil-sulfur corrosion in engineering are mainly aimed at insulating oil. There are two main protective measures for insulating oil: (1) Strict acceptance of new oil: For newly commissioned transformer equipment, it is generally necessary to go through refining and desulfurization treatment and add domestic insulating oil without sulfur antioxidants; for newly imported transformer insulating oil, the IEC 62535-2008 standard (degassing, heating at 150°C for 72 hours) is used to test the corrosion of insulating oil in order to better understand the corrosion of insulating oil. However, this method is costly and inactive sulfur will be converted into active sulfur (1ppm) during operation; (2) Adding metal passivators (BTA, etc.): Metal passivators will react with copper windings to form a protective film on the surface of copper windings, isolating the corrosive sulfur in the insulating oil from direct contact with the metal, thereby preventing corrosion. In addition, the thin film formed by the metal passivator on the metal surface can also react with metal ions in the oil to reduce the concentration of metal ions in the oil. Adding metal passivators to the oil can effectively inhibit the occurrence of corrosion to a certain extent. However, the metal passivators in the oil will be continuously consumed. It is necessary to regularly detect the content of metal passivators in the oil and regularly add metal passivators to the oil. Studies have shown that the stray gases generated by the passivators will dissolve in the insulating oil and interfere with the fault diagnosis results of the dissolved gas in the oil.
[0049] In addition, there are currently few anti-corrosion measures for the copper windings themselves in oil-immersed power equipment. Therefore, it is urgent to propose new anti-corrosion measures for the copper windings themselves to improve the oil-sulfur corrosion resistance of the copper windings, so as to effectively improve the oil-sulfur corrosion resistance of the copper windings.
[0050] In view of this, an embodiment of the present invention provides a copper winding with resistance to oil-sulfur corrosion and a preparation method thereof. By controlling the process parameters of the actual production process of the copper winding in the oil-immersed power equipment, such as the predetermined pass ≥ 4 during rolling, the predetermined temperature ≥ 300°C during annealing, etc., the process parameters for the preparation of the copper winding are optimized, and a copper winding with excellent resistance to oil-sulfur corrosion is obtained through the above-mentioned preparation method of the copper winding with resistance to oil-sulfur corrosion. The oil-sulfur corrosion resistance of the copper winding with resistance to oil-sulfur corrosion provided by the present invention is greatly improved. At the same time, it is based on improving the oil-sulfur corrosion problem of the copper winding in the power equipment from the copper winding itself, and proposes new anti-corrosion measures to improve the oil-sulfur corrosion resistance of the copper winding.
[0051] Figure 1 A flow chart of a method for preparing a copper winding having oil-sulfur corrosion resistance according to an embodiment of the present invention is shown.
[0052] like Figure 1 As shown, the method 100 for preparing a copper winding having oil-sulfur corrosion resistance in this embodiment includes operations S110 to S130.
[0053] In operation S110, the copper strip is rolled according to a predetermined number of passes to obtain a rolled winding.
[0054] In operation S120, the rolled winding is annealed at a predetermined temperature to obtain a copper winding to be processed.
[0055] In operation S130, oxides attached to the surface of the copper winding to be processed are removed to obtain a copper winding having oil-sulfur corrosion resistance.
[0056] According to an embodiment of the present invention, the predetermined number of passes during copper bar rolling is ≥4. When the predetermined number of passes is ≥4, the corrosion resistance of the winding is greatly improved.
[0057] Figure 2 A relationship diagram between the predetermined pass number and the content of special grain boundaries inside the winding according to an embodiment of the present invention is shown.
[0058] like Figure 2 As shown in the figure, with the increase of the predetermined number of passes during rolling, the content of special grain boundaries inside the winding increases first and then decreases. When the predetermined number of passes is greater than or equal to 4, the content of special grain boundaries in the winding increases significantly (all greater than 40%). In particular, when the predetermined number of passes is 5, the content of special grain boundaries in the winding is the highest, which is 51.9%.
[0059] The electrochemical polarization curves of the windings rolled according to different predetermined passes were obtained through electrochemical corrosion tests.
[0060] Figure 3 The electrochemical polarization curves of the windings obtained by rolling with different predetermined passes according to the embodiment of the present invention are shown.
[0061] Table 1 shows the test results of the winding electrochemical corrosion test under different predetermined passes.
[0062]
[0063] Depend on Figure 3 From the electrochemical corrosion test results in Table 1, it can be seen that with the increase of the predetermined number of passes, the increase in the content of special grain boundaries inside the winding causes the corrosion potential in the polarization curve to gradually shift positively, which indicates that the corrosion tendency of the copper winding is reduced and it is less prone to corrosion. When the predetermined number of passes is 3, due to the increase in the content of special grain boundaries, the oil-sulfur corrosion resistance of the winding is improved to a certain extent, and its corrosion potential shifts positively by 0.06 V; when the predetermined number of passes is ≥4, the corrosion potential of the winding continues to increase, and the maximum corrosion potential of the winding with a predetermined number of passes of 5 is -0.219 V, and the corrosion resistance of the windings with 4 to 7 passes is not much different.
[0064] It can be seen from this that when preparing the winding, the rolling number ≥ 4 can improve the corrosion resistance of the material. The more special grain boundaries there are inside the winding, the better the corrosion resistance of the winding.
[0065] Since the present invention is aimed at the oil-sulfur corrosion problem of copper windings in oil-immersed power equipment, the copper windings should also have excellent oil-sulfur corrosion resistance.
[0066] According to the IEC 62535 standard, the oil-sulfur corrosion test was carried out at 150°C for 3 days with a concentration of 500 mg / kg of DBDS. After the corrosion test, the insulating oil was allowed to cool naturally and the copper winding was removed in time after cooling. First, the copper content in the insulating oil after corrosion and the copper content on the insulating paper were tested.
[0067] Figure 4 The copper content test results of the windings obtained by rolling with different predetermined passes according to the embodiment of the present invention are shown.
[0068] like Figure 4 As shown in the figure, with the increase of the scheduled passes, the content of special grain boundaries inside the winding gradually increases, and the content of copper in the insulating oil and on the insulating paper gradually decreases. The winding with the scheduled pass of 1 has the highest copper content, which are 1.183 mg / kg (in oil) and 8.179 mg / kg (on paper) respectively; the winding with the scheduled pass of 5 has the lowest copper content, which are 0.119 mg / kg and 1.126 mg / kg respectively. When the scheduled passes are further increased, the copper content in the oil / on paper increases slightly. When the scheduled passes are 3, the resistance of the winding to oil-sulfur corrosion is improved to a certain extent. When the scheduled passes are ≥4, the resistance of the copper winding to oil-sulfur corrosion is greatly improved, and the copper content is greatly reduced.
[0069] After the test is completed, the winding is taken out and a series of relevant electrical performance tests are carried out on the insulating oil, including breakdown voltage, dielectric loss and volume resistivity tests.
[0070] Figure 5 The breakdown voltage test results of the insulating oil after different predetermined test passes according to the embodiment of the present invention are shown.
[0071] like Figure 5 As shown in the figure, with the increase of the number of predetermined passes, the content of special grain boundaries inside the winding gradually increases, and the breakdown voltage of the copper winding of the insulating oil gradually increases. The content of special grain boundaries in the winding when the predetermined pass is 5 is the largest, so the winding has the best sulfur corrosion resistance, and the insulation oil breakdown voltage is 46.5 kV. When the predetermined pass is ≥4, the breakdown voltage of the copper winding is also greatly improved. This is because the existence of special grain boundaries will interrupt the network connectivity of random grain boundaries. During the test, the greater the content of special grain boundaries in the winding, the greater the probability and number of random grain boundary connectivity interruptions. This is because the interruption of connectivity helps prevent the initiation and expansion of corrosion cracks, thereby improving the sulfur corrosion resistance of the copper winding and increasing the electrical properties of the insulating oil.
[0072] The results of dielectric loss and volume resistivity are important indicators of the performance of insulating oil, and can also reflect the degree of corrosion of the winding.
[0073] Figure 6 The dielectric loss test results of the insulating oil after different predetermined test passes according to the embodiment of the present invention are shown.
[0074] like Figure 6 As shown in the figure, the dielectric loss of the insulating oil of the winding with a predetermined pass of 1 is 0.687 at the maximum. As the number of predetermined passes increases, the content of special grain boundaries in the winding increases, and the dielectric loss begins to decrease. The content of special grain boundaries in the winding with a predetermined pass of 5 is the largest, and the dielectric loss in the insulating oil is as low as 0.163. When the predetermined pass is ≥4, the content of special grain boundaries in the winding increases significantly, its ability to resist oil-sulfur corrosion also increases significantly, and the dielectric loss in the insulating oil is greatly reduced.
[0075] Figure 7 The volume resistivity test results of the insulating oil after different predetermined test passes according to the embodiment of the present invention are shown.
[0076] like Figure 7 As shown in the figure, the change trend of volume resistivity is completely opposite to the dielectric loss performance of insulating oil, that is, with the increase of special grain boundary content, the volume resistivity of insulating oil shows an upward trend. The volume resistivity of the winding with the predetermined pass number 1 is the smallest, which is 85.88×10 9 Ω·m; when the predetermined pass is ≥4, the content of special grain boundaries in the winding increases significantly, so the volume resistivity of the winding also increases significantly; among them, the volume resistivity of the winding with a predetermined pass of 5 is the largest, which is 254.59×10 9 Ω·m.
[0077] According to an embodiment of the present invention, the winding is annealed at a predetermined temperature, and the predetermined temperature is ≥ 300° C. For example, the annealing temperature may be 300° C., 400° C., 500° C., 600° C., and the like.
[0078] According to an embodiment of the present invention, by controlling the process parameters of the actual production process of the copper winding in the oil-immersed power equipment, such as the predetermined number of passes ≥ 4 during rolling, the predetermined temperature ≥ 300°C during annealing, etc., the process parameters for the preparation of the copper winding are optimized, and the copper winding with excellent resistance to oil-sulfur corrosion is obtained by the above-mentioned preparation method of the copper winding with resistance to oil-sulfur corrosion. The oil-sulfur corrosion resistance of the copper winding with resistance to oil-sulfur corrosion provided by the present invention is greatly improved, and at the same time, based on improving the oil-sulfur corrosion problem of the copper winding in the power equipment from the copper winding itself, a new anti-corrosion measure to improve the oil-sulfur corrosion resistance of the copper winding is proposed.
[0079] According to an embodiment of the present invention, the rolled winding is annealed at a predetermined temperature to obtain the copper winding to be processed, including: annealing the rolled winding at a predetermined temperature for a predetermined time to obtain the copper winding to be processed; wherein the predetermined time is ≥30min.
[0080] For example, the scheduled duration can be 30 minutes, 40 minutes, 50 minutes, 60 minutes, etc.
[0081] According to an embodiment of the present invention, the predetermined duration represents the annealing time. As an essential process parameter in the annealing process, the annealing time affects the oil-sulfur corrosion resistance of the winding to a certain extent. Under different annealing times, the content of special grain boundaries formed inside the winding will change accordingly. Therefore, selecting a suitable annealing time is helpful to prepare a winding with high oil-sulfur corrosion resistance.
[0082] According to an embodiment of the present invention, the rolled winding is annealed at a predetermined temperature, wherein the predetermined temperature comprises 300-600°C.
[0083] The special grain boundary contents in the original winding (without deformation and annealing treatment) and the windings made at different annealing temperatures (the deformation amount was 25% and the annealing time was 30 min) were tested.
[0084] Table 2 shows the proportion of special grain boundary content in the winding at different annealing temperatures:
[0085]
[0086] As shown in Table 2, with the increase of annealing temperature, the content of special grain boundaries inside the copper winding first increases and then decreases. Among them, the special grain boundary content of winding No. 5 is the highest, which is 53.8%. Winding No. 1 is the original winding, and the special grain boundary content is the lowest, which is only 4.3%. The special grain boundary content inside the winding can be increased to varying degrees through annealing treatment.
[0087] The electrochemical polarization curves of the original winding and the copper winding prepared at different annealing temperatures were obtained through electrochemical corrosion tests.
[0088] Figure 8 The electrochemical polarization curves of the windings obtained at different annealing temperatures according to the embodiment of the present invention are shown.
[0089] like Figure 8 As shown in the figure, with the increase of the special grain boundary content inside the winding, the corrosion potential in the polarization curve shifts positively, which means that the corrosion tendency of the copper winding is reduced and it is less likely to corrode. The corrosion current density in the polarization curve is an important parameter for judging the degree of metal corrosion and its corrosion rate. With the increase of the special grain boundary content, the corrosion current density gradually decreases, indicating that with the increase of the special grain boundary content of the copper winding, the corrosion rate of the copper winding gradually decreases.
[0090] Table 3 shows the test results of winding electrochemical corrosion test at different annealing temperatures.
[0091]
[0092] It can be seen from Table 3 that the original winding corrosion potential is -0.313 V and the corrosion current density is 2.31×10 -6 A / cm 2 Compared with winding No. 2, the corrosion potential shifted positively by 0.022 V, indicating that deformation and annealing treatment improved the corrosion resistance of the copper winding. From the perspective of windings No. 2 and No. 3, the corrosion potential of winding No. 2 is -0.291 V, and the corrosion current density is 1.04×10 -6 A / cm 2 The corrosion potential of winding No. 3 is -0.289 V, and its corrosion potential has a positive shift of 0.002 V. The corrosion current density is 9.75×10 -7 A / cm 2 The Σ3 grain boundaries of the two windings are not much different. Although the No. 3 winding has more Σ9 grain boundaries, the corrosion resistance of the two windings is not much different. From the perspective of No. 3 and No. 6 windings, the corrosion potential of No. 6 winding is -0.227 V. Compared with No. 3 winding, its corrosion potential has a positive shift of 0.062 V, and the corrosion current density is 2.65×10 -7 A / cm 2 The Σ9 grain boundaries of the two windings are not much different. The No. 6 winding has more Σ3 grain boundaries, which is 31.01%. Its corrosion potential is high and the corrosion current density is small. This shows that when the content of Σ9 grain boundaries in the winding is roughly equal, the more Σ3 grain boundaries, the smaller the corrosion tendency of the winding, and the better the corrosion resistance. The increase in the content of Σ3 grain boundaries helps to reduce the corrosion tendency of the copper winding. Similarly, from the perspective of windings No. 4 and No. 5, the corrosion potential of winding No. 4 is -0.225 V, and the corrosion current density is 1.39×10 -7 A / cm 2 The corrosion potential of winding No. 5 is -0.217 V, and the corrosion current density is 7.18×10 -8 A / cm 2 Since winding No. 5 has more Σ3 grain boundaries inside, it has better corrosion resistance.
[0093] The presence of high-content Σ3 grain boundaries greatly improves the performance of the material. The more special grain boundaries there are inside the copper winding, especially the more Σ3 grain boundaries, the better the corrosion resistance of the winding.
[0094] According to the IEC 62535 standard, the oil-sulfur corrosion test was carried out at 150°C for 3 days with a concentration of 500 mg / kg of DBDS. After the corrosion test, the insulating oil was allowed to cool naturally and the copper winding was removed in time after cooling. First, the copper content in the insulating oil after corrosion and the copper content on the insulating paper were tested.
[0095] Fig. 9 The copper content test results of the windings obtained at different annealing temperatures according to the embodiment of the present invention are shown.
[0096] like Fig. 9 As shown in the figure, with the increase of the content of special grain boundaries inside the winding, the copper content in the insulating oil and on the insulating paper gradually decreases. The No. 1 winding (original winding) is the highest, which are 1.987 mg / kg and 9.774 mg / kg respectively. The No. 5 winding (annealing temperature is 500℃) has the best oil-sulfur corrosion resistance and the lowest copper content, which are 0.097 mg / kg and 1.032 mg / kg respectively. When the temperature rises again, the copper content in the oil / on the paper begins to increase again. When the Σ3 grain boundary is greater than 30%, the oil-sulfur corrosion resistance of the copper winding is greatly improved, and the copper content is greatly reduced.
[0097] The electrical properties of the windings at different setback temperatures were tested.
[0098] Fig.10 The breakdown voltage test results of the insulating oil after different annealing temperature tests according to the embodiments of the present invention are shown.
[0099] like Fig.10 As shown in the figure, with the increase of special grain boundary content and Σ3 grain boundary in the winding, the breakdown voltage of the copper winding of the insulating oil gradually increases. The No. 5 winding (annealing temperature is 500℃) has the largest content of special grain boundaries and the largest number of Σ3 grain boundaries. Therefore, the winding has the best sulfur corrosion resistance, and the insulating oil breakdown voltage is 47.7 kV. The Σ3 grain boundaries of No. 2 winding (annealing temperature is 200℃) and No. 3 winding (annealing temperature is 250℃) are not much different, and the breakdown voltage of the insulating oil is also not much different, which are 20.8 kV and 21.1 kV respectively. When the Σ3 grain boundary is greater than 30%, the breakdown voltage of the copper winding is also greatly improved compared with the original winding (15.8 kV). This is because the existence of special grain boundaries will interrupt the network connectivity of random grain boundaries. During the test, the greater the content of special grain boundaries in the winding, the greater the probability and number of random grain boundary connectivity being interrupted. This is because the interruption of connectivity helps prevent the initiation and expansion of corrosion cracks, thereby improving the sulfur corrosion resistance of the copper winding and increasing the electrical properties of the insulating oil.
[0100] Fig.11 The dielectric loss test results of the insulating oil after different annealing temperature tests according to the embodiments of the present invention are shown.
[0101] like Fig.11 As shown in the figure, the dielectric loss of the insulating oil of winding No. 1 (original winding) is 0.609 at most. With the increase of annealing temperature, the number of Σ3 grain boundaries inside the winding increases, and the dielectric loss begins to decrease. The Σ3 grain boundary content of winding No. 3 (annealing temperature is 250℃) is not much different from that of winding No. 2, and the dielectric loss of the insulating oil is also similar, 0.609 and 0.593 respectively. With the further increase of Σ3 grain boundaries, when the Σ3 grain boundaries inside the winding are greater than 30%, the dielectric loss of the insulating oil drops significantly. Among them, the Σ3 grain boundary content of copper winding No. 5 is up to 47.78%, and the dielectric loss in the insulating oil is as low as 0.152. With the increase of special grain boundaries and Σ3 grain boundary content in the winding, the dielectric loss of the insulating oil gradually decreases, which can effectively reduce the power consumption and heat generation of the transformer during operation.
[0102] Fig.12 The volume resistivity test results of the insulating oil after different annealing temperature tests according to the embodiments of the present invention are shown.
[0103] like Fig.12 As shown, winding No. 1 (original winding) has the smallest volume resistivity, which is 78.56×10 9 Ω·m, the Σ3 grain boundary of winding No. 2 (annealing temperature is 200℃) and winding No. 3 (annealing temperature is 250℃) are not much different, and the volume resistivity of insulating oil is also similar, which is 97.3×10 9 Ω·m and 99.1×10 9 Ω·m; As the Σ3 grain boundaries further increase to more than 30%, the volume resistivity of the insulating oil also increases significantly. Among them, the Σ3 grain boundaries of winding No. 5 are the largest, which is 47.78%. Therefore, the volume resistivity of its insulating oil is the largest, which is 243.67×10 9 Ω·m, the volume resistivity of the other two windings is slightly lower than that of winding No. 5, but both are higher than 200×10 9 The increase of Σ3 grain boundary content improves the oil-sulfur corrosion resistance of copper windings. Therefore, the corrosion degree of windings is low after the corrosion test, the insulating oil still maintains a high volume resistivity, and the insulating performance of the insulating oil is still good.
[0104] The performance of the insulating paper can also reflect the severity of sulfur corrosion on the copper winding. The thermal conductivity of the insulating paper on the winding was tested at different annealing temperatures.
[0105] Fig.13 The thermal conductivity test results of the insulation paper at different annealing temperatures according to the embodiments of the present invention are shown.
[0106] like Fig.13As shown in the figure, the thermal conductivity of winding No. 1 (original winding) is the lowest, which is 0.087. The Σ3 grain boundaries of winding No. 2 (annealing temperature is 200℃) and winding No. 3 (annealing temperature is 250℃) are not much different, and the thermal conductivity of insulation paper is also similar, which is 0.110 W / (m×K) and 0.113 W / (m×K) respectively. As the Σ3 grain boundaries increase to more than 30%, the thermal conductivity of insulation paper also increases. Among them, winding No. 5 has the most Σ3 grain boundaries, so its thermal conductivity of insulation paper is the largest, which is 0.143 W / (m×K). The thermal conductivity of the other two windings is also high, which is 0.138 W / (m×K) and 0.131 W / (m×K) respectively. As the content of Σ3 grain boundaries increases, the corrosion degree of copper winding decreases, so the thermal conductivity of insulation paper will increase.
[0107] Fig.14 The results of the polymerization degree test of the insulating paper at different annealing temperatures according to the embodiment of the present invention are shown.
[0108] like Fig.14 As shown in the figure, the thermal conductivity shows the same rule. The higher the content of special grain boundaries in the winding, the more Σ3 grain boundaries there are, and the lower the corrosion degree of the copper winding. Therefore, the greater the degree of polymerization of the insulation paper, the better the performance of the insulation paper. When the content of Σ3 grain boundaries in winding No. 5 (annealing temperature is 500℃) is 47.78%, the degree of polymerization of the insulation paper is the largest, which is 649. When the content of Σ3 grain boundaries is greater than 30%, the degree of polymerization of the insulation paper is also high, all greater than 550.
[0109] According to an embodiment of the present invention, the corrosion resistance of the windings prepared at different annealing temperatures is evaluated by testing the content of special grain boundaries, electrochemical polarization curves, copper content on insulating paper / oil after the test, electrical properties of insulating paper oil after the test, and properties of insulating paper after the test. The results show that when the No. 5 winding (annealing temperature is 500°C), the corrosion resistance is the best. Selecting a suitable annealing temperature helps to improve the oil-sulfur corrosion resistance of the prepared winding.
[0110] According to an embodiment of the present invention, the deformation of the winding after rolling is ≥20%.
[0111] For example: the deformation of the winding can be 20%, 30%, 40%, 50%, 60%, etc.
[0112] Windings with different deformation amounts have different grain sizes and contents of special grain boundaries. It can be seen that reasonable selection of deformation amount is also one of the important process parameters for preparing windings with excellent resistance to oil-sulfur corrosion, which helps to prepare windings with high resistance to oil-sulfur corrosion.
[0113] According to an embodiment of another aspect of the present invention, based on a method for preparing a copper winding resistant to oil-sulfur corrosion, a copper winding resistant to oil-sulfur corrosion is provided, wherein the Σ3 grain boundary content in the copper winding resistant to oil-sulfur corrosion is greater than 30%.
[0114] According to an embodiment of the present invention, when the predetermined number of rolling passes increases, the content of special grain boundaries inside the winding changes accordingly. The CSL grain boundary ratios (Σ3, Σ9 and Σ27) inside the winding obtained with different predetermined numbers of rolling passes were tested.
[0115] Fig.15 A relationship diagram between the predetermined pass number and the CSL grain boundary ratio inside the winding according to an embodiment of the present invention is shown.
[0116] Table 4 shows the corresponding processes and special grain boundary contents of samples with different predetermined passes:
[0117]
[0118] like Fig.15 As shown in Table 4, the changes in the relationship between the predetermined pass and the CSL grain boundary ratio inside the winding and the relationship between the predetermined pass and the special grain boundary content inside the winding are roughly the same. In particular, the increase in the predetermined pass greatly increases the Σ3 grain boundary inside the winding. The Σ3 grain boundary content of the winding with the predetermined pass of 4, 5, 6, and 7 during rolling is greater than 30%.
[0119] According to an embodiment of the present invention, the content of special grain boundaries in the winding changes with the increase of annealing temperature, and the CSL grain boundary ratios (Σ3, Σ9 and Σ27) inside the winding of the original winding (without deformation and annealing treatment) and the winding prepared at different annealing temperatures (the deformation amount is 25% and the annealing time is 30 min) are tested.
[0120] Fig.16 A relationship diagram between the annealing temperature and the CSL grain boundary ratio inside the winding according to an embodiment of the present invention is shown.
[0121] Table 5 shows the corresponding processes and special grain boundary contents of samples with different annealing temperatures:
[0122]
[0123] Annealing treatment can adjust the CSL grain boundary ratio inside the winding, where the CSL grain boundary ratio includes Σ3, Σ9 and Σ27 grain boundary ratios. Fig.16As shown in Table 5, the Σ3 grain boundaries in windings 2 and 3 are roughly equal, but there are more Σ9 grain boundaries in winding 3, which is 7.07%; the Σ9 grain boundaries in windings 4 and 5 are roughly equal, and the Σ9 grain boundaries in windings 3 and 6 are roughly equal, but there are a large number of Σ3 grain boundaries in winding 6, which is 31.11%. It is worth noting that there are a large number of Σ3 grain boundaries in winding 5, which is 47.78%.
[0124] According to the embodiment of the present invention, by studying and testing the CSL grain boundary ratio inside the copper winding prepared at different annealing temperatures and different predetermined passes, it is found that when the predetermined pass is ≥ 4, there are a large number of Σ3 grain boundaries, and the Σ3 grain boundary content is greater than 30%. In addition, when the annealing temperature is 500°C, the Σ3 grain boundary of the winding is the highest, which is 47.78%. From this, the process parameters for preparing a copper winding with excellent oil-sulfur corrosion resistance can be determined, and the oil-sulfur corrosion resistance of the copper winding with oil-sulfur corrosion resistance can be improved.
[0125] According to an embodiment of the present invention, the grain size in the copper winding having oil-sulfur corrosion resistance is greater than 20 μm.
[0126] Fig.17 The graph shows the winding grain size test results at different annealing temperatures according to an embodiment of the present invention.
[0127] The size of the grains inside the winding was tested at different temperatures. Fig.17 As shown in the figure, with the increase of annealing temperature, the grains inside the copper winding gradually become larger. The grain size of winding No. 6 is the largest, which is 27.562 μm. The grain sizes of windings No. 4, 5, and 6 are all greater than 20 μm.
[0128] Table 6 shows the special grain boundary content and grain size in the winding at different annealing temperatures.
[0129]
[0130] According to an embodiment of the present invention, by studying the grain size under different preparation conditions, the law between the grain size and other process parameters is found to determine the preferred grain size and clarify the optimal performance parameters of the copper winding with resistance to oil-sulfur corrosion.
[0131] According to an embodiment of the present invention, when the content of Σ3 grain boundaries is the same, the oil-sulfur corrosion resistance of the copper winding is positively correlated with the grain size. When the grain size is the same, the oil-sulfur corrosion resistance of the copper winding is positively correlated with the content of Σ3 grain boundaries.
[0132] Fig.18a A graph showing the relationship between the content of special grain boundaries inside a winding and the grain size according to an embodiment of the present invention is shown. Fig.18b A graph showing the relationship between the internal grain size of the winding and the special grain boundary content according to an embodiment of the present invention is shown.
[0133] Table 7 shows the grain size and special grain boundary content inside the winding.
[0134]
[0135] like Fig.18a , Fig.18b As shown in Table 7, copper windings with different grain sizes (with approximately the same special grain boundary content) and different special grain boundary contents (with approximately the same grain size) were obtained by adjusting the preparation process of the copper winding. It can be found that there is a relationship between the grain size and the special grain boundary content. The relationship between the two is studied through specific performance tests.
[0136] The electrochemical polarization curves of different copper windings were obtained through electrochemical corrosion tests.
[0137] Fig.19a Electrochemical polarization curves of windings with different grain sizes according to an embodiment of the present invention are shown. Fig.19b Electrochemical polarization curves of windings with different specific grain boundary contents according to an embodiment of the present invention are shown.
[0138] Table 8 shows the electrochemical corrosion test results for different grain sizes / special grain boundary contents.
[0139]
[0140] like Figure 19a-19b As shown in Table 8, with the increase of grain size and special grain boundary content, the corrosion potential in the polarization curve gradually shifts positively, which indicates that the corrosion tendency of the copper winding decreases and the corrosion resistance is improved. When the special grain boundary content is not much different, the larger the grain size, the better the corrosion resistance of the winding. When the grain size is 129.868 μm, the copper winding has the largest corrosion potential of -0.218 V, which is the least prone to corrosion; when the grain size in the winding is roughly the same, the larger the special grain boundary content in the winding, the greater the corrosion potential, and the lower the corrosion tendency. When the special grain boundary content in the winding is as high as 62.1%, the winding corrosion potential is -0.199 V.
[0141] Similarly, the copper content in the insulating oil after corrosion of the copper winding and the copper content on the insulating paper were tested.
[0142] Figure 20a-Figure 20b The test results of the copper element content on the insulating oil / paper with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are respectively shown.
[0143] like Figure 20a-Figure 20bAs shown in the figure, when the content of special grain boundaries is not much different, the larger the grain size, the lower the copper content in the insulation oil and on the insulating paper. The copper content of the copper winding with a grain size of 129.868 μm is the lowest, which is 0.114 mg / kg (in oil) and 1.214 mg / kg (on paper) respectively; when the grain size in the winding is roughly the same, the larger the special grain boundary content in the winding, the least corrosion, which is 0.109 mg / kg (in oil) and 1.132 mg / kg (on paper) respectively. The increase in grain size and special grain boundary content can improve the copper winding's resistance to oil-sulfur corrosion.
[0144] After the test is completed, the copper winding is taken out and a series of relevant electrical performance tests are carried out on the insulating oil.
[0145] Figure 21a-Figure 21b The breakdown voltage test results of insulating oils with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are respectively shown.
[0146] like Figure 21a-21b As shown in the figure, when the special grain boundary content is not much different, the larger the grain size, the better the corrosion resistance of the copper winding, the higher the breakdown voltage, and the copper winding with a grain size of 129.868 μm has the highest breakdown voltage of 45.67 kV; when the grain size in the winding is roughly the same, the larger the special grain boundary content in the winding, the better the corrosion resistance of the copper winding, the higher the breakdown voltage, and the copper winding with a special grain boundary content of 62.1% has the highest breakdown voltage of 48.45 kV. The increase in grain size and special grain boundary content can improve the oil-sulfur corrosion resistance of the copper winding.
[0147] Figure 22a-22b The dielectric loss test results of insulating oils with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are shown respectively.
[0148] like Figure 22a-22b As shown in the figure, when the special grain boundary content is not much different, the larger the grain size, the better the corrosion resistance of the copper winding, the lower the dielectric loss, and the copper winding with a grain size of 129.868 μm has the lowest dielectric loss of 0.173%; when the grain size in the winding is roughly the same, the larger the special grain boundary content in the winding, the better the corrosion resistance of the copper winding, the lower the dielectric loss, and the copper winding with a special grain boundary content of 62.1% has the lowest dielectric loss of 0.157%.
[0149] Figure 23a-23b The volume resistivity test results of insulating oils with different grain sizes and different special grain boundary contents according to the embodiments of the present invention are shown respectively.
[0150] like Figure 23a-23bAs shown in the figure, the change trend of volume resistivity is completely opposite to the dielectric loss performance of insulating oil, that is, as the oil-sulfur corrosion resistance of the winding increases, the volume resistivity of the insulating oil shows an upward trend. It can be seen that when the special grain boundary content is not much different, the larger the grain size, the better the corrosion resistance of the copper winding, and the lower the volume resistivity. The copper winding with a grain size of 129.868 μm has the highest volume resistivity, which is 253.68×10 9 Ω·m; when the grain size in the winding is roughly the same, the greater the content of special grain boundaries in the winding, the better the corrosion resistance of the copper winding and the higher the volume resistivity. The copper winding with a special grain boundary content of 62.1% has the lowest volume resistivity of 2567.86×10 9 Ω·m.
[0151] According to an embodiment of the present invention, the electrochemical corrosion resistance of windings with different grain sizes and different special grain boundary contents is tested, the copper content of the insulating oil / paper after the test, the dielectric loss and volume resistivity of the insulating oil / paper after the test are tested, and the relationship between the winding grain size and the special grain boundary content is analyzed and evaluated. It is found that when the Σ3 grain boundary content is the same, the oil-sulfur corrosion resistance of the copper winding is positively correlated with the grain size. When the grain size is the same, the oil-sulfur corrosion resistance of the copper winding is positively correlated with the Σ3 grain boundary content. The above rules provide guiding directions for the regulation of process parameters for preparing windings with excellent oil-sulfur corrosion resistance.
[0152] According to an embodiment of the present invention, the electrical properties of the oil-sulfur corrosion resistant winding are obtained based on the research and testing of the predetermined pass, annealing temperature, annealing time, winding deformation, special grain boundary content, and grain size.
[0153] According to an embodiment of the present invention, the corrosion potential of the copper winding includes: -0.21~-0.22V.
[0154] According to an embodiment of the present invention, the corrosion current density of the copper winding includes: 7.18×10 -8 ~2.65×10 -7 .
[0155] The following describes the preparation process of the copper winding with reference to the preparation method of the copper winding in the real oil-immersed power equipment:
[0156] (1) The required materials and equipment are shown in Tables 9 and 10:
[0157] Table 9 shows the materials, equipment and parameters for copper winding preparation.
[0158]
[0159] Table 10 shows the copper winding characterization and test parameters and equipment.
[0160]
[0161] (2) rolling the copper bar at a rolling speed of 0.1-0.3 m / s and a rolling number of ≥ 4;
[0162] (3) After rolling, the winding is placed in an inflatable muffle furnace for annealing at a temperature of 300°C to 600°C, with a maximum operating temperature of 1200°C;
[0163] (4) After annealing, polish the copper strip with sandpaper to remove the surface oxide, wrap it with insulating paper, and fix it to obtain the copper winding used in the test.
[0164] (5) The effects of different process parameters and influencing factors on the oil-sulfur corrosion resistance of the winding were studied: the effect of annealing temperature on the CSL grain boundary ratio, the effect of rolling pass on the CSL grain boundary ratio, and the effect of grain size and special grain boundary content.
[0165] Among them, for the corrosion test, the test conditions are: 500 mg / kg DBDS, corrosion at 150℃ for 72 h. For the electrochemical corrosion test, the following steps are included: ① Pretreatment: Cut the copper winding sample into 10 mm×10 mm block samples, and then use the epoxy resin mixture to embed the cut small samples so that the area outside the resin is 100 mm 2 , and the copper wire was welded to the non-exposed surface of the sample. The prepared sample was polished with 120 mesh, 400 mesh, 800 mesh, 1500 mesh, and 3000 mesh silicon carbide sandpaper until the surface was smooth and flat, and then polished with a polishing machine. The polishing agent used the particle size of 6 μm and 2 μm respectively, and polished until the scratches were invisible to the naked eye. The polished sample was cleaned with alcohol and then blown dry with a blower for the next step of electrolytic polishing. The voltage of electrolytic polishing was 20 kV. Liquid nitrogen was used to maintain the entire electrolytic polishing at -20 °C during the polishing process. The polishing liquid used was a mixed solution of nitric acid and methanol. The duration of electrolytic polishing was generally controlled at about 8~10s;②Corrosion parameters The corrosion electrolyte was NaCl solution, the electrolyte concentration was 0.1 mol / L, the scanning potential range was ±0.3 V of the open circuit potential, and the scanning rate was set to 0.01 mV / s.
[0166] Based on the above copper winding preparation process, compared with the original winding, a copper winding containing more Σ3 grain boundaries (greater than 30%) was obtained by annealing temperature control; from the electrochemical test results of the winding, the copper winding (winding No. 5) with a higher content of special grain boundaries has a higher corrosion potential (-0.217 V) and a lower corrosion current density (7.18×10 -8 A / cm 2), the corrosion tendency is lower, among which Σ3 grain boundary plays a major role. The more Σ3 grain boundaries, the better the corrosion resistance of the winding. The Σ3 grain boundaries of winding No. 5 are the most, accounting for 47.78%; from the copper content in the oil paper after the corrosion test, the No. 5 winding has the best corrosion resistance, and the copper content in the oil paper is the lowest, which are 0.097 mg / kg and 1.032 mg / kg respectively. The copper windings with similar Σ3 grain boundary content also have similar oil-sulfur corrosion resistance (such as windings No. 4 and No. 6); the insulating oil and insulating paper of the copper windings with special grain boundaries and high Σ3 grain boundary content after corrosion still have excellent insulation performance, with breakdown voltage (all greater than 40 kV) and volume resistivity (all greater than 200×109 Ω·m), thermal conductivity (all greater than 0.13) and degree of polymerization of insulating paper (all greater than 550) are all high, proving that the copper winding is not significantly corroded; the grain boundary engineering treatment increases the content of special grain boundaries inside the winding, and the copper winding has more Σ3 grain boundaries (greater than 30%), and its corrosion resistance is better.
[0167] In addition, by comparing the copper windings obtained with different predetermined passes, it was found that when the predetermined pass was ≥ 4, the special grain boundary content of the winding was greatly increased, among which the Σ3 grain boundary had the largest increase (all greater than 40%), and the corrosion resistance was greatly improved. The copper element in the oil was less than 0.16 mg / kg. After the corrosion test, the insulating oil still had excellent insulation properties, and the breakdown voltage (both greater than 40 kV) and volume resistivity (both greater than 200×109 Ω·m) were both high.
[0168] As for the grain size and special grain boundary content, when the special grain boundary content is roughly the same, the larger the grain size, the better the winding's resistance to oil-sulfur corrosion; when the grain size is roughly the same, the larger the special grain boundary content, the better the winding's resistance to oil-sulfur corrosion.
[0169] According to various characterizations and test results, the special grain boundary that can effectively improve the copper winding's resistance to oil-sulfur corrosion is the Σ3 grain boundary, and the minimum predetermined number of passes that can effectively improve the copper winding's resistance to oil-sulfur corrosion is 4. By regulating the annealing temperature during the preparation of the copper winding (the optimal annealing temperature is 300℃~600℃), a copper winding with a high content of special grain boundaries and Σ3 grain boundaries (greater than 30%) can be obtained. The winding's resistance to oil-sulfur corrosion is greatly improved, and the larger the winding grain size, the more special grain boundaries, and the better the winding's resistance to oil-sulfur corrosion. The oil-sulfur corrosion problem can be improved from the winding itself, and it has a high application potential in oil-immersed transformers.
[0170] The embodiments of the present invention are described above. However, these embodiments are only for the purpose of illustration, and are not intended to limit the scope of the present invention. Although each embodiment is described above, it does not mean that the measures in each embodiment cannot be used in combination advantageously. Without departing from the scope of the present invention, those skilled in the art may make various substitutions and modifications, which should all fall within the scope of the present invention.
Claims
1. A copper winding with resistance to oil-sulfur corrosion, characterized in that: include: The Σ3 grain boundary content in the copper winding with oil-sulfur corrosion resistance is greater than 30%; when the Σ9 grain boundary content in the copper winding is equal, the more the Σ3 grain boundary content, the better the corrosion resistance of the copper winding; Under the condition that the Σ3 grain boundary content is the same, the oil-sulfur corrosion resistance of the oil-sulfur corrosion-resistant copper winding is positively correlated with the grain size; in order to improve the corrosion resistance of the copper winding, the grain size is set to 129.868 μm; Under the condition that the grain size is the same, the oil-sulfur corrosion resistance of the copper winding with oil-sulfur corrosion resistance is positively correlated with the Σ3 grain boundary content; in order to improve the corrosion resistance of the copper winding, the special grain boundary content is set to 62.1%; Wherein, the method for producing a copper winding having resistance to oil-sulfur corrosion comprises: Rolling the copper bar according to a predetermined number of passes to obtain a rolled winding; wherein the predetermined number of passes is ≥ 4; Annealing the rolled winding at a predetermined temperature to obtain a copper winding to be processed; wherein the predetermined temperature is ≥300°C; The oxide attached to the surface of the copper winding to be treated is removed to obtain a copper winding resistant to oil-sulfur corrosion; wherein the annealing treatment is used to regulate the grain boundary content in the copper winding.
2. The copper winding with oil-sulfur corrosion resistance according to claim 1 is characterized in that: The step of annealing the rolled winding at a predetermined temperature to obtain a copper winding to be processed comprises: The rolled winding is annealed at a predetermined temperature for a predetermined time to obtain the copper winding to be processed; wherein the predetermined time is ≥30 min.
3. The copper winding with oil-sulfur corrosion resistance according to claim 1 is characterized in that: The predetermined temperature includes 300-600°C.
4. The copper winding with oil-sulfur corrosion resistance according to claim 1 is characterized in that: The deformation of the winding after rolling is ≥20%.
5. The copper winding with oil-sulfur corrosion resistance according to claim 1 is characterized in that: The corrosion potential of the copper winding having resistance to oil-sulfur corrosion ranges from -0.21 to -0.22V.
6. The copper winding with oil-sulfur corrosion resistance according to claim 1 is characterized in that: The corrosion current density of the copper winding having resistance to oil-sulfur corrosion includes: 7.18×10 -8 ~2.65×10 -7 A / cm 2 。
Citation Information
Patent Citations
Method for improving corrosion resistance of copper winding
CN117393311A